The First Successful Heart-Lung Transplant in a Korean Child with Humidifier Disinfectant-Associated Interstitial Lung Disease - Jhang, Won Kyoung; Park, Seong Jong; Lee, Eun; Yang, Song I; Hong, Soo Jong; Seo, Ju-Hee; Kim, Hyung-Young; Park, Jeong-Jun; Yun, Tae-Jin; Kim, Hyeong Ryul; Kim, Yong-Hee; Kim, Dong Kwan; et al. (Journal of Korean medical science, 2016)
From 2006 to 2011, an outbreak of a particular type of childhood interstitial lung disease occurred in Korea. The condition was intractable and progressed to severe respiratory failure, with a high mortality rate. Moreover, in several familial cases, the disease affected young women and children simultaneously. Epidemiologic, animal, and post-interventional studies identified the cause as inhalation of humidifier disinfectants. Here, we report a 4-year-old girl who suffered from severe progressive respiratory failure. She could survive by 100 days of extracorporeal membrane oxygenation support and finally, underwent heart-lung transplantation. This is the first successful pediatric heart-lung transplantation carried out in Korea.